Relationship of Workplace Culture on Employee Performance: The Case of a Higher Education Institution in the Philippines - Angelou C. Almendras; Jesus P. Briones; Flormando P. Baldovino; Lalaine V. Manalo (People and Behavior Analysis, 2025)
Workplace culture drives the transformation of individual employee performance. This study assessed the workplace culture across four dimensions in terms of communication, leadership, teamwork, and recognition, and determined its relationship with employee performance in terms of motivation, job satisfaction, and productivity. This descriptive-quantitative study employed a researcher-structured approach to examine the relationship of workplace culture on employee performance in a higher education institution (HEI) in the Philippines. The data were collected from 56 employees of the subject HEI using a researcher-structured questionnaire administered in-person. Statistical tests such as frequency, percentage, weighted mean, and multiple regression analysis using Partial Least Square SEM were employed in the data analysis. The findings revealed that the HEI has an appropriate and relevant workplace culture supportive of achieving common goals and making employees productively engaged in their work, though the employee performance can still be improved. Likewise, the study also confirmed that workplace culture is significantly related to employee performance in terms of productivity. On the other hand, no significant relationships exist between the dimensions of workplace culture and the motivation and job satisfaction dimensions of employee performance were revealed. While problems related to workplace culture rarely occur in the HEI, the researchers suggest a strategy roadmap for a more positive workplace culture to further improve employee performance. This study can be used as a reference in formulating workplace culture enhancement measures to increase employee performance.